Cutaneous neoplasms of uncertain differentiation. Issue 1 (January 2022) - Morgan, Ceri; Hallin, Magnus; Fisher, Cyril; Thway, Khin
Abstract: Tumours of uncertain differentiation represent a markedly heterogeneous group of neoplasms that show no identifiable line of differentiation by currently available technologies, and do not resemble any specific normal cells or tissues. Continuing advances in molecular genetics have significantly aided to our understanding of these tumours, enabling refinements in classification and better insights into their biology, and furthering the development of ancillary immunohistochemical and molecular diagnostic tests and targeted therapies in the clinical setting. This review summarizes key genetic, morphologic and immunohistochemical features for a selection of cutaneous neoplasms of uncertain differentiation, with emphasis on new entities and developments in the diagnostic setting.